1978
DOI: 10.2307/1165863
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Analysis of Some Procedures to Teach Priming and Reinforcement Skills to Preschool Teachers

Abstract: This Monograph reports the results of teaching preschool teachers to be successful at increasing desired behaviors of their children, thus becoming successful teachers. Five teacher-training techniques were examined experimentally under single-subject designs: written assignments, feedback from viewing graphs, on-the-spot feedback from a wireless radio (Bug-in-the-Ear), feedback from an observer, and self-counting. Those teaching procedures that included prompt and frequent information to the teacher about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 14 publications
1
21
1
Order By: Relevance
“…Our qualitative findings regarding ongoing participation differed from those reported by Thomson et al (1978), which indicated participants disliked the BIE after prolonged use. Scheeler et al (2009), too, found that at least one teacher participant grew tired of the BIE as time went on.…”
Section: Perceptions Regarding Prolonged Use and Thoughts About Ongoicontrasting
confidence: 99%
“…Our qualitative findings regarding ongoing participation differed from those reported by Thomson et al (1978), which indicated participants disliked the BIE after prolonged use. Scheeler et al (2009), too, found that at least one teacher participant grew tired of the BIE as time went on.…”
Section: Perceptions Regarding Prolonged Use and Thoughts About Ongoicontrasting
confidence: 99%
“…Numerous research studies have demonstrated the superiority of direct training procedures over didactic training procedures for enhancing skill development Mueller et al, 2003;Rickert et al, 1988;Sterling-Turner, Watson, Wildmon, Watkins, & Little, 2001;Watson & Kramer, 1995). Additionally, training studies evaluating direct and didactic training procedures for increasing teacher implementation of classroom-based intervention procedures have found similar results (Fantuzzo et al, 1996;Sterling-Turner et al, 2001;Sloat, Tharp, & Gallimore, 1977;Stormont, Covington-Smith, & Lewis, 2007;Thomson, Cooper-Holmberg, & Baer, 1978). It is important to note that direct training studies involving teachers and classroom-based interventions have often included training procedures that occurred outside of routine classroom activities.…”
Section: Procedures For Increasing Treatment Integritymentioning
confidence: 99%
“…Training type has been shown to be an important variable when considering impact on subsequent teacher intervention implementation. Direct training procedures have been shown to be superior to didactic training when impact on teacher implementation of classroom interventions has been monitored (Fantuzzo et al, 1996;Sloat et al, 1977;Sterling-Turner et al, 2002;Stormont et al, 2007;Thomson et al, 1978). Most direct training procedures in teacher training studies have occurred outside the context of normal classroom activities and have included performance feedback or additional components (e.g., implementation scripts) in addition to training.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…The school experience encourages children to analyze, conceptualize, and generalize. Schooling with respect to opportunities and methods of acquiring specific cognitive skills affects cognitive development more than the difference in culture or social class (Stevenson et al, 1978). …”
Section: Discussionmentioning
confidence: 99%
“…As a product of the interaction of environment with nervous system the child acquires basic skills and knowledge of the culture and internalizes behavioral patterns from the particular social context. Children’s opportunities to acquire specific memory and cognitive skills from schooling and from their general experience in a particular environment affect cognitive development (Stevenson et al, 1978). Differences in performance have been observed with 2–3 years of schooling (Nisbett and Norenzayan, 2002).…”
Section: Introductionmentioning
confidence: 99%